Where all light tends to go [large type] - Joy, David, 1983- (Center Point Large Print, 2015)
"Set in North Carolina's Appalachian Mountains, eighteen-year-old Jacob McNeely is torn between appeasing his meth-dealing kingpin father and leaving the mountains forever with the girl he loves"--